2022
DOI: 10.37859/jpumri.v6i1.3551
|View full text |Cite
|
Sign up to set email alerts
|

Penyuluhan Digital Untuk SMP YWKA 2

Abstract: This Community Service activity aims to introduce Schoology as a digital classroom platform to improve the quality of educators in teaching. This activity involved two lecturers and one student from Indraprasta University PGRI. The target participants of this community service activity are junior high school educators Yayasan Wanita Kereta Api II Jakarta. This activity was attended by 11 teachers of SMP YWKA 2 Pulogadung, East Jakarta. The approach used is Andragogy. Andragogy as the art and science of helping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…In addition, written online media, liputan6.com was also found using vocabulary construction to make classifications (Saputri., et al 2022), In other words, the selection of vocabulary by liputan6.com that has an impact on classifying the reader's thinking is also found in the news of the Omicron variant in Indonesia delivered during January 2022. Based on the data collected, it was found that as many as 6 data from 34 units of data that included vocabulary construction criteria making classifications.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, written online media, liputan6.com was also found using vocabulary construction to make classifications (Saputri., et al 2022), In other words, the selection of vocabulary by liputan6.com that has an impact on classifying the reader's thinking is also found in the news of the Omicron variant in Indonesia delivered during January 2022. Based on the data collected, it was found that as many as 6 data from 34 units of data that included vocabulary construction criteria making classifications.…”
Section: Resultsmentioning
confidence: 99%
“…Saat ini Kurikulum sudah beralih pada kurikulum merdeka yang dapat mengoptimalkan siswa untuk belajar. Pergantian kurikulum juga mengakibatkan berubah cara belajar, dan metode belajar yang bergeser dari metode tradisional ke metode yang bersifat digital (Saputri, Widiyarto, Nugroho, & Hadi, 2022). Perkembangan dunia digital juga menjadi alasan munculnya metode belajar yang interaktif dan diminati siswa maupun guru (Fahrudin & Pamungkas, 2022).…”
Section: A Pendahuluanunclassified
“…Siswa dan guru memerlukan waktu dan tenaga agar dapat menyesuaikan kurikulum yang baru. Siswa dan guru tetap diharuskan belajar (Saputri et al, 2022). Jika metode yang digunakan tidak memotivasi siswa, maka banyak dijumpai siswa belajar kurang semangat dan sering tidur di kelas (Fauziah, 2013).…”
Section: A Pendahuluanunclassified
“…Hasil dari survei yang dilakukan oleh Kementerian kominfo, menunjukkan 5 media sosial terpopuler di Indonesia, yaitu Facebook (65 juta pengguna), Twitter (19,5 juta pengguna), Google+ (3,4 juta pengguna), LinkedIn (1 juta pengguna), dan Path (700ribu pengguna). Penggunaan teknologi akan memudahkan pengguna untuk berinteraksi dan dapat diandalkan [4]. Namun permasalahan yang timbul pada penggunaan media sosial dan beberapa aplikasi komunikasi antara lain berupa peleburan ruang privat dengan ruang publik para penggunanya.…”
Section: Pendahuluanunclassified